Extra-oral verruciform xanthoma: an uncommon entity - Jain, Akanksha; Agarwal, Shilpi; Nain, Manupriya; singh, Deeksha (Annals of Pathology and Laboratory Medicine, 2014)
Verruciform xanthoma (VX) is an uncommon benign condition, which frequently affects the oral mucosa in adults. Only few cases of VX of anogenital region and skin have been reported. Clinically, it presents as a white or yellowish-white sessile or pedunculated, papillary or verrucous mucosal growth and is usually less than 2 cm in size. Although it is considered a benign entity, it has clinical importance as it needs to be differentiated with wart like growths i.e. verrucous carcinoma, condyloma acuminatum, seborrheic keratosis and due to its strong association with more serious diseases like epidermolysis bullosa, epithelial dysplasia, pemphigus vulgaris,Â solar keratosis andÂ discoid lupus erythematosus. The etiology of this lesion is unknown, however is thought to be reactive rather than a neoplastic process secondary to epithelial damage induced by different associated conditions. We present two cases of VX and discuss their clinical and histopathological findings and possible correlation with a postulated etiopathogenesis.